Restaging the Conquest of Michoacán in the 1990’s: Víctor Castillo Bautista’s Nuño de Guzmán o la espada de Dios - Hernández, Mark A. (Latin American Theatre Review, 2003)
The years leading up to the 1992 Quincentennial of Columbus’ first voyage saw an increase in Latin American plays representing the discovery, exploration and conquest of the Americas. While numerous plays focus on figures and episodes related to the fall of Tenochtitlán, Víctor Castillo Bautista’s Nuño de Guzmán o la espada de Dios: una obra en un acto (1994) centers on the Spanish conquistador Nuño de Guzmán and the conquest of Michoacán. By restaging the conquest of Michoacán and the execution of the Cazonci, which have been featured as prime exhibits for accusations against Guzmán of excessive cruelty, the play puts into question one-dimensional ideological interpretations of this episode, which traditionally portray the conquistadors as pure evil and the Amerindians as unwitting and passive victims in their demise. In the end, the play alters our understanding of Guzmán and the conquest of Michoacán. (MAH, in Spanish)